Structure-based drug design targeting infectious disease - Duffy, Erin (Henry Stewart Talks, 2008)
Many antibiotics inhibit the ribosome, Intelligent engine builds perpetual pipeline, Crystallography shows 50S is a target-of-targets, From new X-ray crystals to new leads, Analog(Trade Mark), LINKER essentials: tethering two binding features, BOMB essentials, MUSIC essentials: core-swapping, QikProp: calculating drug-like properties, Structures + Analog(Trade Mark): balanced compounds, Case study: enhanced oxazolidinones, Structural foundations, Path to enhanced oxazolidinones, Pi contributions represent key interactions, Probing selectivity of sparsomycin, Seeking a new lead, Difference density map showing rib-X prototype, Perfect match, A minimal scaffold for lead optimization, Minimal scaffold binds effectively in A-site, Activity against H. influenzae, H. influenzae activity with time evolution, H. flu model delivers differentiable oxazolidinones, Moderate in vivo activity measured, Predictive model for rat oral bioavailability, First pool of drug candidates, Structures + predictive models = time-saving filters